The Man from Red Vienna - Kuttner, Robert (New York Review of Books, 2017)
A review of the book "Karl Polanyi: A Life on the Left," by Gareth Dale, is presented.
N/A
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); book review; great powers (international relations); nonfiction

Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Sociology; Geography
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

Market fundamentalism in the age of 'haute finance': The enclosing of policy space in 'emerging' India - Lakshminarayan, Srivatsan (Ephemera: Theory & Politics in Organization, 2017)
The rise of the Emerging Market is a remarkable exemplar of an idea that originated and was socialized in Western financial markets during the 1980s. It has since gained rapid, wider normative status with respect to a particular set of beliefs that motivate policy choices on macroeconomic management, economic development and financial sector reforms in developing and less developed countries. I draw on the Polanyian notion of commodification and recent extensions to his scholarship in the realm of ideas that seek to explicate processes through which the dominant ideal of the self-regulating market is justified as fundamental to the organization of society. Against the backdrop of globally mobile capital, I critique the prevalence of a particular ideology of emergence in which commodified geography and commodified finance interact to shape policy. In this process, evaluative talk plays a key role in legitimizing the expectations of global capital and overcoming inherent contradictions through the rhetoric of non-crises. I thus highlight the ascendance of a narrow and instrumentally economic understanding of emergence in contemporary, post reform India as is asserted in conventional policy discourse. I conclude by remarking on the significant constriction of ideational space for the consideration of alternative, historically informed approaches to social and economic development. The legacy of Karl Polanyi serves as a prophetic reminder for the consequences of such constriction.
Management Studies
Keywords: India; commodification; economic development; emerging markets; haute finance; macroeconomics

Family as a Socio-economic Actor in the Political Economies of East and South East Asian Welfare Capitalisms - Papadopoulos, Theodoros; Roumpakis, Antonios (Social Policy & Administration, 2017)
In this article, we revisit Karl Polanyi's concept of 'oikos' in order to reconceptualize the role of the family as both a welfare provider and an economic actor in the social reproduction of East and South East Asian welfare capitalisms. Our article is structured in four parts. First, we critically review existing approaches on the characteristics of welfare capitalism in East and South East Asia. We argue that existing approaches tend to isolate family as a welfare provider and neglect how the role of the family is institutionalized as a collective actor. The second part focuses on the role of the family in the social reproduction of welfare capitalism, and explores how, in East and South East Asia, the specific conditions for family's role as an economic actor were institutionalized historically. The third part revisits Polanyi's concept of 'oikos' and how 'householding' constitutes one of the most important forms of economic action allowing us to examine the family as a socio-economic actor. In the fourth section, we provide an analysis of families' available strategies and discuss evidence related to private education expenditure, household debt and labour market income share. We conclude by highlighting the need to re-articulate the importance of family as a collective socio-economic actor that, despite recent reforms and path departures, remains at the epicentre of East and South East Asian welfare capitalisms.
Political Science; Public Administration
Keywords: East and South East Asia; OIKOS (The Greek word); debt; economic conditions in Asia; families & economics; family; households and economics; social reproduction; welfare capitalism; welfare state

'Playing on the break': Karl Polanyi and the double-movement 'Against Modern Football' - Webber, David M (International Review for the Sociology of Sport, 2017)
While the popularity of English football increases worldwide, there has been a marked rise in the discontent expressed by a small but growing group of domestic fans. This dissent has led to the emergence of a movement broadly defined as being 'Against Modern Football' (AMF), a banner under which fans of rival clubs have gathered in an attempt to challenge the poor governance, commercialism and greed that has come to dominate the English game. This article offers a conceptualisation of what it means to be 'against modern football' based upon Karl Polanyi's analysis of the market society. Developing the dialectic of the 'double-movement' that appears in Polanyi's most famous work, The Great Transformation, this article demonstrates how these governing principles might be useful in explaining both the complex cultural political economy of English football and the possibilities that exist for the AMF movement to socially re-embed the modern game.
Sociology
Keywords: English football; athletic clubs; cultural political economy; soccer; sociology of sport; sports - social aspects; sports spectators; supporters

"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought – from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp – than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view – that is, to a radical approach to Polanyi's thought.
History; Economics
Keywords: Poor Law; WEBER; Max; 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Why TTIP is an unprecedented geopolitical game-changer, but not a Polanyian moment - Eliasson, Leif Johan; García-Duran, Patricia (Journal of European Public Policy, 2017)
This contribution argues that the Transatlantic Trade and Investment Partnership (TTIP) is unprecedented, not because it constitutes a Polanyian moment, but rather because it offers an alternative to multilateralism through the World Trade Organization (WTO). Never before has bilateralism offered such a 'best alternative to no agreement' (BATNA) to members of the core decision-making body of the WTO negotiating arm, making TTIP an unprecedented geopolitical game-changer. The anti-TTIP campaign, however, has not been driven by concerns with either geopolitics or trade liberalization, but rather fears about the European Union's (EU's) bargaining power. By strategically focusing on the potential impact on public policy and safety standards, normative arguments promulgated by opponents reflect concerns with perceived threats to the status quo and a willingness to preserve the same. The United States is presented (implicitly) as more powerful than the EU, and therefore perceived as able to impose its preferences, which are considered too neoliberal.
Political Science
Keywords: European Union; TTIP; Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); bilateralism; free trade; geopolitics; trade

Markets, Knowledge and Human Nature: Friedrich Hayek, Karl Polanyi and Twentieth-century Debates on Modern Social Order - Innset, Ola (European History Quarterly, 2017)
The article reads the works of Friedrich Hayek (1899-1992) and Karl Polanyi (1886-1964) in the light of their political commitments to neoliberalism and socialism respectively. It argues that both thinkers were inspired to explain history and recent events in line with these commitments in their 1944 publications, The Road to Serfdom and The Great Transformation. Furthermore, they both developed their most significant insights by attempting to counter perceived challenges from political projects to which they were opposed. Polanyi spent much of his life trying to disprove a liberal attack on socialism as out of touch with the realities of human nature, whereas it was in debates with socialists that Hayek developed a new theory of the epistemological functioning of markets, which then became foundational for the neoliberal project. Taking into account the high-stakes politics of Vienna in the interwar years is crucial for fully understanding the social theory of these two thinkers.
History
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; human behavior; knowledge; markets; neoliberalism; social order; socialist accounting; socialist calculation debate; totalitarianism

Fictitious Freedom: A Polanyian Critique of the Republican Revival - Klein, Steven (American Journal of Political Science, 2017)
Prominent republican theorists invoke anonymous orders such as the market as mechanisms that secure freedom as non-domination. Drawing on Karl Polanyi's account of fictitious commodities and demonstration of the impossibility of a just and rational market society, this article critically scrutinizes neo-republican assumptions regarding the market, develops an alternate social theory within which to situate the ideal of non-domination, and illustrates the importance of this reconfiguration for the kind of collective agents and political strategies that can be expected to advance republican freedom in the economy.
Political Science
Keywords: Polanyi - political & social views; economic liberty; markets; republicanism; social theory

Unpacking the objectives and assumptions underpinning European aquaculture - Ertör, Irmak; Ortega-Cerdà, Miquel (Environmental Politics, 2017)
Increasing demand for seafood and the lack of growth of capture fisheries have boosted aquaculture growth worldwide. However, European aquaculture has been stagnating over the past decade, and European public authorities have been developing policies and strategies in efforts to reverse this. Aquaculture discourses in the European Union, based on 34 policy, planning, and strategy documents, are examined and a discourse analysis conducted following Bacchi's WPR (What is the Problem Represented to be?) approach. How the problems in these discourses are represented, the tensions among main objectives, and the implicit assumptions are unveiled, and discussed employing a Polanyian theoretical framework. Taking these assumptions for granted leads to a disembedded understanding of aquaculture, and facilitates the privatization of aquatic space and resources. The analysis contributes to the literature establishing the link between the expansion of aquaculture and the enclosure of aquatic resources and enriches environmental and political debates on European aquaculture.
Environmental Science
Keywords: Europe; European Union law; aquaculture; aquatic resources; discourse analysis; enclosures; environmental politics; fisheries; fishery policy; government policy; privatization

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
History; Sociology
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Commodifying art, Chinese style: The making of China’s visual art market - Zhang, Jun (Environment & Planning A, 2017)
The economic value of art to cities and regions has recently been vigorously pursued and actively studied. The rapid ascendance of China as a superpower in the global art market and associated transformation of China’s art space, however, are yet poorly understood. This paper develops a Polanyian framework to interpret the spatial and institutional evolution of China’s art market, seeing the (de)commodification of art as a cumulative process embedded in geo-historical interplays of triple logics—cultural, capital, and political, unfolding within, and reshaping in turn, historically inherited spatial structures.
Geogrpahy
Keywords: China; Chinese art; art - economic aspects; art industry; art market; commodification; cultural and creative industries; public art spaces

Re-reading Friedrich Hayek and Karl Polanyi in the Late-Modern Condition of Fragility - Cha, Taesuh (Political Studies Review, 2017)
The cardinal role of complexity in Friedrich Hayek’s theory of the market has hardly gone unnoticed. Indeed, there is now a considerable corpus of literature that has established the importance of spontaneity as a central concept around which neoliberal economic theory revolves. However, as William Connolly analyzes, its closed conception of economic processes simplifies real economic volatilities and ignores both modes of self-organization and creativity found in democracy and social movements that periodically irrupt into market processes. This article builds upon this critique of neoliberalism and employs Karl Polanyi’s genealogy of modern capitalism to understand historical imbrications between the market and the social and their contribution to the fragility of capitalism. Polanyi’s notions of “(dis-)embeddedness” and the “double movement” not only show us a more “complex” view of modern political economy but also provide us with important lessons for political responses to the recent crisis of neoliberal capitalism.
Political Science
Keywords: CONNOLLY; William; Friedrich Hayek; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; capitalism; complexity (philosophy); complexity theory; fragility; genealogy

When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Political Science
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union; 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism

Karl Polanyi in an Age of Uncertainty - Block, Fred; Somers, Margaret R. (Contemporary Sociology, 2017)
Sociology
Keywords: DALE; Gareth; For a New West: Essays 1919-1958 (Book); Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; book review; nonfiction; socialism

The Great Recurrence: Karl Polanyi and the crises of the European Union - Goldmann, Matthias (European Law Journal, 2017)
In his seminal 1944 book The Great Transformation, Polanyi describes the rise and fall of liberal capitalism during the long nineteenth century. Many have realised that Polanyi has a lot to tell about the European Union in the aftermath of the financial crisis. The paper begins with an overview of Polanyi's historiography of the failure of nineteenth-century liberal capitalism and his account of the four elements that helped liberal capitalism thrive, while precipitating its collapse-the idea of the self-regulating market, the gold standard, international peace and liberal constitutionalism. Thereafter, the paper describes the particular transformations that these four elements underwent in the course of European integration and after the financial crisis, with a particular focus on the case law of the Court of Justice. The paper argues that their current constellation has a destructive potential that exceeds the economic dimension of the Union and might pave the way for a much greater failure, one that might defeat Europe's greatest success: the establishment of peace. Ultimately, the paper assesses current reform proposals in light of these insights and makes a number of proposals for re-embedding the economy in society.
Law
Keywords: European Union - politics & government; European Union countries; Great Transformation; The (Book); capitalism; embeddedness

The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Political Sciences; Development Studies
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

The Second Time Around? Polanyi and Today's Fascist Tendency - Sandbrook, Richard (Peace Magazine, 2017)
Discusses the relevance of Polanyi’s double movement in light of increasing support for far-right, authoritarian and neo-fascist movements in Europe and North America. The author quotes The Great Transformation on how fascism “was rooted in a market system that refused to function” (21), however, he chooses to center his analysis on an unpublished essay of Polanyi’s entitled “The Fascist Virus”. From this, he extrapolates that fascism operates like a disease within liberal capitalism, becoming lethal when tensions between capitalism and democracy hit crisis levels and unleashing itself into the body politic (20).
Peace Studies
Keywords: fascism; right-wing populism

Producers' cooperation within or against cooperative agricultural institutions? The case of reindeer husbandry in Post-Soviet Russia - Vladimirova, Vladislava (Journal of Rural Studies, 2017)
With the advance of economic neoliberalization along with the green economy paradigm that aims to alleviate rapid climate change, discussions of the rationale of cooperative organization of food production have come to the fore. This paper contributes to the scholarly understanding of motivations for cooperative organization of production by taking up empirical illustrations from the European North of Russia, where despite expectations of privatization after the dissolution of the Soviet Union, the cooperative organization of reindeer husbandry often persists, as a heritage of the Soviet state enterprises ( sovkhozes ). The paper aims at advancing the analysis of cooperative reindeer husbandry and its rationales employing ideas within the field of substantivist economic anthropology of postsocialism that started with Karl Polanyi's vision of the embedded economy (Polanyi, 1944). Further, I have employed the ideas of the renowned study by Caroline Humphrey of Soviet state farms as total social institutions (Humphrey, 1998) as well as Stephen Gudeman's dialectical approach to the economy (Gudeman, 2001). The analysis shows that the cooperative organization of reindeer husbandry reproduces the economic and social patterns that were developed in the Soviet period, perhaps also adapting and incorporating elements of traditional indigenous social orders. Such social arrangements and the accompanying moral values are embedded in the reindeer herding economy, and it is their persistence that indigenous people achieve through adhering to cooperative values.
Anthropology; Rural Studies
Keywords: Eurasian studies; agricultural societies; agriculture - Russia; cooperative organization; embedded economy; farmers & the environment; food production - environmental aspects; reindeer farming; substantivism

Earth Incorporated: Centralization and Variegation in the Global Company Network - Haberly, Daniel; Wójcik, Dariusz (Economic Geography, 2017)
Over the past twenty years, a widening gulf has appeared between the increasingly internationalized financing arrangements of the world’s leading corporations and the persistence of nationally compartmentalized approaches to the study of corporate control. In lieu of direct empirical evidence on corporate control at the global level, the most widespread assumption is that the globalization of ownership has taken the form of an expansion of arm’s-length, market-based arrangements traditionally prevailing in the Anglo-American economies. Here, however, we challenge this assumption, both empirically and conceptually. Empirically, we show that three-quarters of the world’s 205 largest firms by sales are linked to a single global company network of concentrated (5 percent) ownership ties. This network has a hierarchically centralized organization, with a dominantglobal network coreof US fund managers ringed by a more geographically diversestate capitalist periphery. Conceptually, we argue that the this architecture can be broadly explained through a Polanyianvariegated capitalistmodel of contradictory market institutionalization, with the formation of the global company network actually a counterintuitive product of global financial marketization. In order to understand this process of network formation, however, it is necessary to extend Polanyi’s model of a double movement, mediated through political interventions in the market, to incorporate Veblenian processes of evolutionary institutional change, mediated through the market.
Geography
Keywords: asset management; asset management concentration; corporate ownership internationalization; evolutionary economic geography; evolutionary economics; financialization; global company network; globalization; sovereign wealth funds; state capitalism; stock ownership; variegated capitalism

Institutional Matrices Theory, or X- and Y-Theory: A Response to F. Gregory Hayden - Kirdina-Chandler, Svetlana (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article draws attention to issues about the institutional matrices theory (IMT) as perceived by and raised in the article by F. Gregory Hayden. To clarify the “controversial” points, I structure my response narrative along two lines. First, I present the prehistory of IMT, or X- and Y- theory, including earlier work by scientists related to the concept of institutional matrix. I connect the development of the actual IMT with the period of “perestroika” and the associated market experiments and reforms in Russia and Eastern European countries. One could see that the effects of market reforms in Russia were different in comparison with other countries in economic transition. I show that the institutional approach was accepted as more relevant to understanding the unexpected results in Russian society. I present IMT as a development of the ideas of Karl Polanyi and Douglas North to answer the challenges of explaining the real social and economic processes in Russia, as well as its wider application to a broader range of economic and social situations in different countries. Second, I then present the main IMT theses, giving special attention to the issues as perceived and raised by Hayden. In conclusion, I suggest the possibility of a joint project that combines IMT consideration and the social fabric matrix (SFM) concept of F. Gregory Hayden.
Economics
Keywords: HAYDEN; F. Gregory; Perestroika; Russia; economic policy; economics; institutional matrices theory; reciprocity

Karl Polanyi: A Life on the Left - Kurtz, Geoffrey (New Political Science, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); book review

An anthropological reading of the policies of international development: export competitiveness as a conjunctural case study - Shakya, Mallika (Dialectical Anthropology, 2017)
Drawing on ethnography of the World Bank's private sector development program, this paper explores the ways in which discussions of export competitiveness emerged in the past decade or so and how they interacted with larger discourses on solidarity and development. The immediate context within which this idea emerged was that of the structural adjustment programs (SAPs) which had maintained that the public regulation of the private economy compromises on industrial productivity (and by extension distributive social justice). But it would be naïve to think that alternative ideologies have not tried to insert themselves within the Bank's neoliberal discourse on development. If anything, discursive narratives suggest that the very notion of export competitiveness initially worked to justify the role of the state in regulating and incubating the private sector in developing countries even if these attempts became disembedded from their local contexts in the long run. This paper contextualizes this specific encounter on export competitiveness within the broader discourse of development and economic anthropology to examine the discursive politics of policy and knowledge in the global aid industry.
Anthropology
Keywords: IFIs; World Bank; anthropology; competition (economics); competitiveness; development; disembeddedness; economic liberalization; embeddedness; ethnology; human economy; structural adjustment program (SAP)

Polanyi, the Failed Prophet of Moral Economics - Adelman, Jeremy (Boston Review, 2017)
Polanyi gave us a vital counterpoint to the hegemony of political economics. But how far can he take us?
N/A
Keywords: biography; critique

What American Government Does - Luger, Stan; Waddell, Brian (JHU Press, 2017)
It has become all too easy to disparage the role of the US government today. Many Americans are influenced by a simplistic anti-government ideology that is itself driven by a desire to roll back the more democratically responsive aspects of public policy. But government has improved the lives of Americans in numerous ways, from providing income, food, education, housing, and healthcare support, to ensuring cleaner air, water, and food, to providing a vast infrastructure upon which economic growth depends. In What American Government Does, Stan Luger and Brian Waddell offer a practical understanding of the scope and function of American governance. They present a historical overview of the development of US governance that is rooted in the theoretical work of Charles Tilly, Karl Polanyi, and Michael Mann. Touching on everything from taxes, welfare, and national and domestic security to the government’s regulatory, developmental, and global responsibilities, each chapter covers a main function of American government and explains how it emerged and then evolved over time. Luger and Waddell are careful to both identify the controversies related to what government does and those areas of government that should elicit concern and vigilance. Analyzing the functions of the US government in terms of both a tug-of-war and a collaboration between state and societal forces, they provide a reading of American political development that dispels the myth of a weak, minimal, non-interventionist state. What American Government Does represents a major contribution to the scholarly debate on the nature of the American state and the exercise of power in America. – Sidney Plotkin, Vassar College, coauthor of Private Interests, Public Spending: Balanced-Budget Conservatism and the Fiscal Crisis
Political Science
Keywords: American government; history - Americas (North; Central; South; West Indies); political science - history and theory

Food industry structure in Norway and Denmark since the 1990s: Path dependency and institutional trajectories in Nordic food markets - Klimek, Bjørn; Hansen, Henning Otte (Food Policy, 2017)
Structural changes in Norwegian and Danish food industry since the 1990s is analysed as a path dependent response to the neo-liberal turn. Norway entered the 1990s as a protected market and Denmark as case of an export oriented industry. These developmental strategies are rooted in early 20th century industrialisation and influenced by institutional transformations in the 1990s, such as EU and WTO. Mergers and acquisitions (M&A) are studied in the context of changing political environments. Explaining two different trajectories, we combine path dependency theories and a Polanyi inspired ‘varieties of capitalism’ framework with corporate strategy theories on food industry M&As. We identify two different types of path dependent development, a self-reinforcing in Denmark and a transformative ‘breaking point’ in Norway.
Economics
Keywords: Nordic food markets; World Trade Organization (WTO); agri-food chain; business planning; food economics; food industry - economic aspects; food industry structure; food marketing; food mergers and acquisitions (M&A); food policy; food supply management; institutional change; path dependency

Free market ideology and deregulation in Colorado’s oil fields: Evidence for triple movement activism? - Malin, Stephanie A.; Mayer, Adam; Shreeve, Kelly; Olson-Hazboun, Shawn K.; Adgate, John (Environmental Politics, 2017)
Unconventional oil and gas extraction (UOGE) has spurred an unprecedented boom in onshore production in the US. Despite a surge in related research, a void exists regarding inquiries into policy outcomes and perceptions. To address this, support for federal regulatory exemptions for UOGE is examined using survey data collected in 2015 from two Northern Colorado communities. Current regulatory exemptions for UOGE can be understood as components of broader societal processes of neoliberalization. Free market ideology increases public support for federal regulatory exemptions for UOGE. Perceived negative impacts do not necessarily drive people to support increased federal regulation. Utilizing neo-Polanyian theory, interaction between free market ideology and perceived negative impacts is explored. Free market ideology appears to moderate people’s views of regulation:increasingthe effect of perceived negative impacts while simultaneously increasing support forderegulation. To conclude, the ways in which free market ideology might normalize the impacts of UOGE activity are discussed.
Sociology
Keywords: Colorado; deregulation - government policy; double movement; environmental sociology; fracking; free enterprise; free markets; gas extraction; hydraulic fracturing; market ideology; neoliberalism; oil fields; public support; triple movement; unconventional oil and gas production

CSR as a legitimatizing tool in carbon market: Evidence from Latin America’s Clean Development Mechanism - Benites-Lazaro, L.l.; Mello-Théry, N.A. (Journal of Cleaner Production, 2017)
Clean Development Mechanism (CDM) has incorporated sustainable development as one of their objectives. This objective gives companies an increasing motivation to contribute to sustainable development through their corporate social responsibility (CSR). However, perceived profitability of companies with carbon commodification were negatively associated with CDM projects. This paper aims to identify CSR activities in CDM in three Latin American countries, namely, Brazil, Mexico, and Peru and understand the drivers behind of these CSR initiatives. The study is based on the evaluation of 593 projects registered and Polanyi’s theory. We identified some CSR activities corresponding to the social, environmental and economic indicators in the three countries. This is not to say that all CDM developers are acting in a socially responsible manner. Certain CSR activities in most of the cases were implemented as a way to legitimize and as a means to achieve social acceptance.
Environmental Studies; Sustainability Studies
Keywords: CSR; Latin America; carbon dioxide mitigation; clean development mechanism; corporate legitimacy; corporate social responsibility; double movement; double-movement; economic aspects; embeddedness; emission control; social acceptance; social responsibility of business

Fixing network failures? The contested case of the American Manufacturing Extension Partnership - Brandt, Philipp; Whitford, Josh (Socio-Economic Review, 2017)
The article uses a case study of the American Manufacturing Extension Partnership to explore economic and industrial policy in the contemporary USA. Extensive quantitative and qualitative data are mobilized to show that: (a) the agency is pressured politically to limit its activities to 'blunt' remedies for identifiable 'market failures'; even as (b) regional centers in fact often orient also, and sometimes instead, toward 'coordination-oriented' policies to mitigate 'network failures'; and (c) these latter generate better results, on average, for client manufacturers. The findings challenge neo-institutional claims that economic policies are most effective only when complementary to the dominant institutional coordinating capacities embedded in the existing American political economy, or when they have the exceptional support of the American security establishment. They are, however, consistent with an alternative neo-Polanyian approach that explains when and how streetlevel policymakers dispersed across American federalism sometimes sidestep the ideological hegemony of 'market fundamentalism'.
Sociology
Keywords: United States; economic policy; embeddedness; industrial organization; industrial policy; institutional complementarity; manufactures; market failure; market fundamentalism; partnership (business); public policy; regional economies

Karl Polanyi: A Life on the Left - Innset, Ola (European History Quarterly, 2017)
History
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); nonfiction

It's not the Cases, It's the System - Koskenniemi, Martti (Journal of World Investment & Trade, 2017)
M. Sornarajah's recent analysis of investment arbitration as an offshoot of 'neoliberalism' is basically correct. But it attaches too much importance to the bias of the arbitrators and the procedural problems in arbitral practice. The controversy over the Trans-Pacific Partnership (TPP), the Transatlantic Trade and Investment Partnership (TTIP) and investment arbitration generally is not about the niceties of arbitral procedure, the discretion of arbitrators or the pros and cons of the European Union proposed 'investment court'. The significance of investment arbitration has to do with the many ways in which already the very presence of a 'dis-embedded' and one-sided system of claims automatically skews public policies in favour of foreign investors. The juristic debate is but the surface of struggle over the role of public power and democratic governance of domestic and global economy.
Law
Keywords: General Agreement on Tariffs and Trade (GATT); Sornarajah; Trans-Pacific Partnership (TPP); Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); arbitration & award lawsuits; fair and equitable treatment; investment arbitration; investments - lawsuits & claims; neoliberalism

Reproducing spaces of embeddedness through Islamic NGOs in Sub-Saharan Africa: reflections on the post-2015 development agenda - Tok, M. Evren; O’Bright, Ben (African Geographical Review, 2017)
This paper explores the nexus of religion, space, and development. It sheds light on the role of faith-based organizations (FBOs) as partners in sustainable development and key actors for achieving the Sustainable Development Goals in sub-Saharan Africa (SSA). Applying and building on the theoretical framework of Polanyi’sThe Great Transformationindicates that FBOs with value-laden agendas have formed new state spaces during the age of globalization, where state capacities are transferred to non-state actors at other levels. The case study of Qatari organizations in SSA demonstrates how their uptake of state capacities can lead to development efforts that are driven by faith apart from politics and economics, which help balance market liberalism and social protectionism to create the conditions for sustainable development. Among other things, FBOs offer alternative financing options and new opportunities for financial inclusion that are relevant to the implementation of the post-2015 development agenda.
Geography; African Studies
Keywords: Africa; Qatar; development; economic development; embeddedness; faith based NGOs; faith based human services; state spaces; sustainable development

Finance proud and industry vulnerable: When governments fail to defend the economic realm, citizens revolt - Pettifor, Ann (Juncture, 2017)
The subordination of society to self-regulating international markets is the reason why British workers and industries so often fall prey to predatory financiers, writes Ann Pettifor. It is also a fundamental cause of current political crises throughout the west – just as Karl Polanyi described almost 80 years ago.
Economics
Keywords: private equity firms; self-regulating market

Re-dynamising Local Economies in the Age of Trumpism - Bauwens, Michel; Niaros, Vasilis (Journal of Futures Studies, 2017)
The article presents the authors' arguments on the political and policy response behind the rise of Trumpism according from the analysis of authors Kojin Karatani, Karl Polanyi and Mark Blyth. Topics discussed include Karatani's book "The Structure of World History" on the integration of modalities for political and economic system, Polanyi's analysis in the book "The Great Transformation" on the systemic balance and the transition in regimes of value for re-alignment of modalities.
Futures Studies
Keywords: BLYTH; Mark; Futures studies; Great Transformation; The (Book); KARATANI; Kojin; Structure of World History: From Modes of Production to Modes of Exchange; The (Book); TRUMP; Donald; Trumpism; disembeddedness; local economies; technology

Polanyi and Foucault on the Issue of Market in Classical Political Economy: Complementary Approaches to the Radical Theory of Social Control - Guizzo, Danielle; de Lima, Iara Vigo (Review of Radical Political Economics, 2017)
Studies have pointed out that the value of markets is related to their impact on the character of a society. Karl Polanyi's thesis about social disembeddedness attributed to 19th century economic liberalism the responsibility for consolidating the process of separating markets from society, which changed the dynamics between the state and population when economic rationality began dictating their connections. However, Polanyi only suggested analyses regarding power relations between these three elements and their effects on the social context. This paper argues that Michel Foucault's writings concerning technologies of power and biopolitics complement Polanyi's considerations insofar as they provide an understanding about how biopolitics emerged and how this led to a new posture of the state regarding population care and economic environment regulation.
Economics
Keywords: FOUCAULT; Michel; 1926-1984; biopolitics; classical economic liberalism; embeddedness; liberalism; political science; sociobiology; socioeconomic theory; socioeconomics

Lawyers’ Empire and The Great Transformation - Harris, Douglas C. (International Journal of the Legal Profession, 2017)
A literary criticism of the book "Lawyers' Empire: Legal Professions and Cultural Authority" by Canadian lawyer W. Wesley Pue is presented. It outlines economic historian Karl Polanyi's assumption of Great Transformation in Western Europe that made the period of Pue's book long. It examines lawyers being innovators in Canada.
Law
Keywords: Canada; Lawyers' Empire: Legal Professions & Cultural Authority (Book); PUE; W. Wesley; Western Europe; lawyers

Karl Polanyi on economy and society: a critical analysis of core concepts - Hodgson, Geoffrey M. (Review of Social Economy, 2017)
The article presents the views of economic historian Karl Polanyi on the nature of economic and social embeddedness. Topics discussed include relationship between the economic and social embeddedness, the impact of the market economy, the transformation of society and production of material goods. Particular focus on limits of privatization, commodification, and marketization.
Economics
Keywords: business; capitalism; commodification; economic; economic activity; embeddedness; markets; social

The four modes of coexistence in social systems - Nechansky, Helmut (Kybernetes, 2017)
Purpose The paper aims to relate the four modes of coexistence of goal-orientated systems – conflict, hierarchy, the niche and cooperation – to static behavioral descriptions of social systems.Design/methodology/approach Analyzing the options for interactions of goal-orientated systems leads the four modes of coexistence. These show certain behavioral characteristics. Searching for these characteristics in selected behavioral descriptions in organizational theory, sociology, political science and system science allows relating them to certain modes.Findings In organizations, the four modes of coexistence show in general (Cameron and Quinn) and dyadic interaction patterns (Argyris). In sociology, they show in educational schemes preparing for specific modes (Bernstein) and in different exchange patterns (Polanyi). In political theory, the four modes of coexistence show in preferred policies of parties, in institutional development, in oligarch power politics (Winters) and in external policy. In system science, they show in problem solving strategies (Jackson) and “mindscapes” (Murayama).Research limitations/implications The analysis is restricted to static patterns leaving out dynamic developments, for example, in networks.Practical implications Together with previous investigations, the paper shows how behavioral descriptions ranging from psychology to politics correspond to the four modes of coexistence, and it suggests interrelations and alignments of the modes via various levels of societal organization.Originality/value The four modes of coexistence provide an unequivocal theoretical framework that allows finding parallels in behavioral descriptions ranging from psychology via sociology to politics.
Sociology
Keywords: business planning; cybernetics; decision making; decision-making; forms of integration; industrial organization (economic theory); interaction; politics; redistribution; sociology; systems theory

Urban Governance in Africa Today: Reframing, Experiences, and Lessons - Obeng-Odoom, Franklin (Growth & Change, 2017)
Progress in analysing the instrumental view of governance as an engine for growth, poverty reduction, and inclusive development has been held back by the difficulty in framing governance. This essay seeks to address this problem by 1) reframing urban governance 2) evaluating its aims, processes, and outcomes, and 3) explaining those outcomes on the basis of which some lessons are teased out. Using examples from Africa and an institutional political economy approach (based on institutional economics, Marxist political economics, Georgist political economics, and Polanyian political economy), I show that, overall, while urban economies are growing; both urban poverty and inequality levels have risen substantially. Urban governance has paved the way for new forms of urban development that only benefit the few. Not only are there differences in how urban services and resources are experienced, accessed, and controlled but the varieties are also socially differentiated. I argue that the underlying reasons for this disjuncture between 'urban governance' in theory and 'actually existing urban governance' are 1) difficulties in implementing urban governance theory consistently in practice, 2) problems arising because urban governance theory has been implemented in practice, 3) tensions that would entangle most policies which do not address historical and structural economic issues, 4) restrictive assumptions, and 5) incoherence among the different dimensions of urban governance. To resolve these contradictions, I put the case for major structural and institutional change involving: 1) the re-ordering of the roles of the state, market, and society as institutions of change; 2) re-working the relationships that bind together land, labour, capital, and the state, and 3) re-organising the channels for keeping the attainment of the ends of urban governance in check.
Development Studies
Keywords: Africa; economic development; economic policy; labor; labour; poverty reduction; public administration

Karl Polanyi: a life on the left - Payne, Anthony (International Affairs, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; biography; book review; economists; nonfiction

Market Liberalism, Marginalised Citizens and Countermovements in India - Sahoo, Sarbeswar (Asian Studies Review, 2017)
How has neo-liberalism transformed the economic structure and policies of India? And what are the politico-economic implications of such policies for marginalised populations? Following Karl Polanyi’s theory of “double movement”, this paper argues that while market liberalism has helped India overcome the slow so-called “Hindu rate of growth”, it has adversely affected the economic interests of the poor. It further argues that the expansion of the market (first movement) has led to various social dislocations in the lives of the poor. Such dislocations have generated several countermovements (second movement), which have found expressions not just in electoral politics but also in various grassroots movements. While it may be true that such countermovements have not always been successful in overturning the tide of neo-liberalism, they have certainly influenced the policy priorities of the state in favour of the poor and the marginalised in India.
Area Studies; Asian Studies
Keywords: India; countermovement; double movement; economic policy; grassroots movements; neoliberalism; political mobilisation; social dislocation; social marginality; social welfare

‘Hipster Capitalism’ in the Age of Austerity? Polanyi Meets Bourdieu’s New Petite Bourgeoisie - Scott, Michael (Cultural Sociology, 2017)
This article dialogues Polanyi and Bourdieu to propose a new research agenda within the sociology of cultural production. Extending recent literature on hipsters, this iconic figure is shifted from the world of consumption to the world of production via Bourdieu’s conceptualisation of the new petite bourgeoisie. Using secondary empirical material of cultural micro-enterprises, two ideal-typical career strategies are sketched: cultural-capital oriented seeking to secure positions within established creative industries, and economic-capital orientated stylising ‘old’ petite bourgeoisie occupations to access economic returns. However, within the context of ongoing austerity policies, Bourdieu’s economic capital does not fully account for the variegated forms of material resources these nascent enterprises draw on. Bringing Polanyi’s modes of economic integration – reciprocity, redistribution and exchange – to Bourdieu opens new questions on how hipster capitalism is the practice of intermediating between these ‘backstage’ material modes and the ‘frontstage’ selling of style.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; austerity; capitalism; cultural capital; cultural production; cultural sociology; hipster; hipsters (subculture); micro-enterprise; modes of economic integration; new cultural economy; new petite bourgeoisie

Cooperate! A paradigm shift for health equity - Wei-Ching Chang; Fraser, Joy H. (International Journal for Equity in Health, 2017)
The role of competition and cooperation in relation to the goal of health equity is examined in this paper. The authors explain why the win-lose mentality associated with avoidable competition is ethically questionable and less effective than cooperation in achieving positive outcomes, particularly as it relates to health and health equity. Competition, which differentiates winners from losers, often with the winner-takes-all reward system, inevitably leads to a few winners and many losers, resulting in social inequality, which, in turn, engenders and perpetuates health inequity. Competitive market-driven approaches to healthcare–brought about by capitalism, neo-liberalization, and globalization, based primarily on a competitive framework–are shown to have contributed to growing inequities with respect to the social determinants of health, and have undermined equal opportunity to access health care and achieve health equity. It is possible to redistribute income and wealth to reduce social inequality, but globalization poses increasing challenges to policy makers. John Stuart Mill provided a passionate, philosophical defense of cooperatives, followed by Karl Polanyi who offered an insightful critique of both state socialism and especially the self-regulating market, thereby opening up the cooperative way of shaping the future. We cite Hannah Arendt's "the banality of evil" to characterize the tragic concept of "ethical fading" witnessed in business and everyday life all over the world, often committed (without thinking and reflecting) by ordinary people under competitive pressures. To promote equity in health for all, we recommend the adoption of a radically new cooperation paradigm, applied whenever possible, to everything in our daily lives.
Health Studies; Medicine
Keywords: capitalism; competition; competition (psychology); cooperation; cooperative movement; cooperativeness; ethical fading; health & social status; health equity; health services accessibility; health status indicators; interpersonal relations; paradigm shift; paradigms (social sciences)

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
History; Education
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS; Bernie; TRUMP; Donald

From supply management to agricultural subsidies—and back again? The U.S. Farm Bill & agrarian (in)viability - Graddy-Lovelace, Garrett; Diamond, Adam (Journal of Rural Studies, 2017)
Farm subsidies have become increasingly maligned in agricultural policy debates, but the merits of subsidies are a distraction from deeper political, economic, and ecological problems in agriculture. Drawing on a history of the U.S. Farm Bill, this paper argues that a fixation on farm subsidies ignores why they came into being, and more generally glosses over the imperative for modern states to intervene into agricultural economies. Karl Polanyi's 'double movement' framework is used to situate the rise and fall of agricultural supply management within food regime theory. In the second, or surplus food regime, the U.S. government wielded excess commodities as geopolitical tools—even as domestic farm policy labored to contain overproduction, and thus support agrarian viability. In the subsequent corporate food regime, “free market” agriculture displaces and discredits supply management, even as massive government intervention into how food is grown and sold continues. Making space to remember historical price support programs, to situate their accomplishments and limitations, and to recognize residual supply-management mechanisms (such as farm cooperatives and agricultural marketing orders) is crucial for fostering agricultural viability in the US and beyond. Twentieth century supply management had flaws, but it cannot be wholly omitted. This paper highlights key motivations, elements, and contradictions of these policies and programs to begin the process of considering how supply management principles and strategies could be updated and enhanced for 21st century agriculture. Such a framework would need to pay more attention to diversity within domestic and international agricultures, and be more sensitive to the multi-scalar dimensions of food systems.
Geography
Keywords: agricultural economics; agricultural subsidies; agriculture & state; business food service; food supply

The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism

Did free market fundamentalism spawn the likes of Donald Trump? - Chakravarty, Manas (http://www.livemint.com/, 2017)
The economy was always embedded in society until capitalism arrived on the scene—this perhaps best explains the rise of Donald Trump
N/A
Keywords: BLOCK; Fred; TRUMP; Donald; double movement; market fundamentalism

Karl Polanyi on the Rise of Fascism and Market Economy - Komlik, Oleg (Economic Sociology and Political Economy, 2017)
A spectre is haunting Europe and the world — the spectre of Fascism (veiled as defensive democracy and common-sense patriotism) and authoritarian neoliberalism (disguised as social protectionism an…
Sociology
Keywords: economic sociology; fascism

Karl Polanyi, The Great Transformation and a New Political Economy - Watson, Matthew; Holmes, Christopher; Clift, Ben (brunobertez, 2017)
Karl Polanyi, The Great Transformation and a new political economy Professor Matthew Watson, Assistant Professor Christopher Holmes and Professor Ben Clift, Politics and International Studies Avert…
Political Science; International Relations
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; MARX; Karl; 1818-1883

Polanyi against the whirlwind - Guinan, Joe; Hanna, Thomas M. (Renewal (0968252X), 2017)
The author argues that market liberalism should be stopped if the 21st century generation is to avoid the re-emergence of fascism and environmental collapse. The author calls on the political left to offer a different political economy to avoid the consequences of market liberalism and warns against economist Karl Polanyi's assertion that market liberalism always leads to the erosion of society's human and natural substance. He also discusses the reasons for the political turmoil in the U.S.
N/A
Keywords: environmental monitoring; fascism; liberalism; market liberalism; right & left (political science)

State–peasant movement relations and the politics of food sovereignty in Mexico and Ecuador - Henderson, Thomas Paul (Journal of Peasant Studies, 2017)
This contribution argues that the articulation between the state and peasant organizations’ internal structures – the class characteristics of their mass bases, their leaderships and the modes of interaction between the two – is critical for determining the nature of contemporary struggles guided by the discourse of food sovereignty. It will show that that counter-hegemonic demands are not synonymous with counter-hegemonic practice; rather than struggling to replace the neoliberal food regime, many peasant organizations employ the food sovereignty discourse as a political tool in their negotiations with the state in order to access resources from within the prevailing neoliberal model, not to transform it.
Development Studies
Keywords: GRAMSCI; Antonio; 1891-1937; Via Campesina; agriculture & state - Ecuador; agriculture & state - Mexico; food regime; food sovereignty; hegemony; peasant organizations; peasant studies

Brexit and its Consequences - Pettifor, Ann (Globalizations, 2017)
In this brief essay, I argue that the ‘Brexit’ vote is but the latest manifestation of popular dissatisfaction with the utopian ideal of autonomous markets beyond the reach of regulatory democracy. Brexit represented the collective, if (to my mind) often misguided, efforts of those ‘left behind’ in Britain to protect themselves from the predatory nature of market fundamentalism. In a Polanyian sense, it is a form of social self-protection from self-regulating markets in money, trade and labour.
Economics
Keywords: BREXIT Referendum; 2016; Brexit; business; countermovement; democracy; double movement; financialization; markets; utopias

Financialization and Society's Protective Response: Reconsidering Karl Polanyi's Double Movement - Watkins, John P. (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Financialization challenges Karl Polanyi's thesis of double movement, the thesis that efforts to extend the market evoke efforts to protect humans, nature, and means of production from market forces. Financialization refers to the increased power of financial institutions. The government protects the incomes and assets of financial institutions, but it does little to protect the incomes and assets of households, which are necessary for people to afford healthcare, education, emergencies, retirement, and so on. Polanyi criticized nineteenthcentury civilization for transforming land, labor, and the means of production into commodities, using economic insecurity to motivate humans. The development of intangible property allowed business to expand the market in two ways: (i) restricting output to drive up profits and (ii) liquefying consumer assets to provide credit to consumers to increase spending. The implications of that process manifested themselves in the financial crisis of 2008. Market capitalism represented the attempt to organize commodities based on economic rationality. Similarly, the twentieth- and twenty-first-century capitalism represents the effort to "rationally" organize society according to the value of intangible assets. Both efforts failed, indicating the continued relevance of Polanyi's thesis.
Economics
Keywords: asset management; commons; double movement; financial services industry; financialization; global financial crisis; 2008-2009; intangible property; socioeconomic factors

Reviving Hayek’s Dream - Worth, Owen (Globalizations, 2017)
This short piece suggests that the roots of the successful Brexit vote can be found in the free market purity that was implicit within the ideals behind Thatcherism. Whilst the rhetoric of populist and British (or in many parts English) nationalism were utilised in order to win support, the ideological driving force implicit within many Brexit figureheads rested in the belief that the EU watered down their visions of a harder neoliberal reality. Yet, by stimulating right-wing reactionary forces, they may have created more than they bargained for. I concur with Karl Polanyi that free market liberalism tends to generate the forces of its own demise.
Political Science
Keywords: Brexit; Brexit Referendum; 2016; free enterprise; liberalism; market idealism; neoliberalism; populism; the far right

The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Sociology
Keywords: Fordism; MARX; Karl; 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Philosophy; Political Science
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

Nancy Fraser and Karl Polanyi. A Possible Dialogue - Brie, Michael (Karl Polanyi in Dialogue: A Socialist Thinker for our Times, 2017)
From the very beginning a misunderstanding has to be cleared up – the reduction of Polanyi’s work to that of a reformer who wants to counter the excesses of market radicalism with social protective measures and believes that the crisis of modern
Philosophy
Keywords: FRASER; Nancy; triple movement

The Elusive Karl Polanyi - Luban, Daniel (Dissent (00123846), 2017)
The article focuses on author Karl Polanyi and his works including "Origins of the Cataclysm," "Freedom from Economics" and "The Liberal Utopia." It mentions the role Polanyi and his works during the Great Recession and in the analysis of the social movement in the age of Porto Alegre and Seattle as they can be compared to a totem for social democracy such as Karl Marx for communism and Hayek for neoliberalism. It adds that during the Great Recession, Polanyi was considered a master theorist of the welfare state. It also cites Polanyi as a social leader and an uneasy fit to a social order.
N/A
Keywords: Liberal Utopia; The (Book); MARX; Karl; 1818-1883; Origins of Cataclysm; authors; authorship; communism; social democracy; social movements

A Foreword to Kari Polanyi Levitt - Rodrick, Dani (Dani Rodrik's weblog, 2017)
I was recently asked to write a foreword to the Mexican edition of Kari Polanyi Levitt’s From the Great Transformation to the Great Financialization. Kari is Karl Polanyi's daughter, and the essays in her book – part memoir, part intellectual...
N/A
Keywords: From the Great Transformation to the Great Financialization (Book); POLANYI LEVITT; Kari; embeddedness; neoliberalism

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism–R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
History; Political Science
Keywords: HENRY; Richard; PALMER; Edward; TAWNEY; R.H.; THOMPSON; E.P.; capitalism; moral and ethical aspects; moral economy; socialism

Deindustrialisation and the Historical Sociological Imagination: Making Sense of Work and Industrial Change - Strangleman, Tim (SOCIOLOGY-THE JOURNAL OF THE BRITISH SOCIOLOGICAL ASSOCIATION, 2017)
Following recent calls for a more self-aware and historically sensitive sociology this article reflects on the concept of deindustrialisation and industrial change in this spirit. Using EP Thompson’s classic The Making of the English Working Class and his examination of industrialising culture with its stress on experience, the article asks how these insights might be of value in understanding contemporary processes of deindustrialisation and work. Drawing on a range of sociological, cultural and literary studies it conceptualises the differences and similarities between two historic moments of industrial change and loss. In particular it draws on the literary concept of the ‘half-life of deindustrialisation’ to explore these periods. The article has important implications for how we think about contemporary and historical industrial decline.
Sociology
Keywords: THOMPSON; E. P. (Edward Palmer); 1924-1993; half-life of deindistrialisation; historical sociology; work meaning and identity

Progressive Responses to Populism: A Polanyian Critique of Liberal Discourse - Yarrow, David (The Political Quarterly, 2017)
This article explores the recent rise of populist politics from the perspective of Karl Polanyi's theory of the ‘double movement’. It firstly introduces Polanyi's understanding of interwar populism, and relates this to his broader critique of liberal economic thought. This framework is then used to analyse three prominent explanations for populism which emerged in the wake of the UK's 2016 EU referendum: globalisation; cultural reaction; and social media. I show how each of these explanations exogenises contemporary populist movements, narrating them as something external to the liberal economic restructuring pursued globally since the 1980s. Failing to diagnose adequately the causes of contemporary populist movements, which lie in this utopian attempt to treat labour as a commodity, they cannot support an intellectually coherent progressive response to Brexit. Finally, I outline a political agenda centred on labour de-commodification, which could directly address populist grievances and reclaim the discourse of ‘taking back control’ for the left.
Political Science
Keywords: Brexit; commodification; double movement; labour; liberal discourse; populism

An Evaluation of Institutional Matrices Theory Which Was Designed to Illustrate Differences Between Russian and Western Political Economies - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article is devoted to the evaluation of the institutional matrices theory (IMT), which was designed to illustrate the differences between Russian and Western political economic systems. IMT has no matrix, and it is an ideological declaration rather than a theory. It is a set of assertions and assumptions that are adopted without evidence, and then hypostatized to be Russian and Western socioeconomic systems. IMT literature claims to utilize the reciprocity, redistribution, and exchange model of Karl Polanyi (1944, 1957). However, IMT suffers from a number of assumptive and methodological problems in its application, the first of which consists of the complete exclusion of reciprocity from consideration. The first section of the article is an explanation of problems with IMT, and the second section demonstrates some particulars of the IMT problems with a real-world social fabric matrix from a Western nation.
Economics
Keywords: Russia; economic policy; economics; institutional economics; institutional matrices theory; social fabric matrix; socioeconomics